2014
DOI: 10.5539/gjhs.v7n2p87
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic Approach to Nursing Education: Lived Experiences of Iranian Nursing Students

Abstract: The nurse teachers tried to have a complete understanding of the educational contents, to transfer knowledge to nursing students better, and to facilitate the process of education. The purpose of this study was to explore the lived experiences of Iranian nursing students regarding the characteristics of academic nurse teachers. In this hermeneutic phenomenological study, data were collected via in-depth, semi-structured interviews with 12 Iranian nursing students and the audio-taped and transcribed interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
1
3
1
Order By: Relevance
“…a few researcher illustrate that according to nursing students, respecting students' personality by giving attention and understanding, respecting time of the nursing students and supporting them are ethical characteristics of academic clinical instructorsin nursing practice. [3] These findings are consistent with previous studies, which revealed that closed relationship and supportive behavior with students encourage their motivation, their work in clinical practice, increases criticism acceptance, better adaptation to stress and giving attention to the educational content obtainable by the clinical instructor. [16,17] Therefore, it is noted that the items in the teaching ability, evaluation and nursing competence respectively,interpersonal relations, and personality categories are nurturing actions consistent with the overall nursing principle of caring.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…a few researcher illustrate that according to nursing students, respecting students' personality by giving attention and understanding, respecting time of the nursing students and supporting them are ethical characteristics of academic clinical instructorsin nursing practice. [3] These findings are consistent with previous studies, which revealed that closed relationship and supportive behavior with students encourage their motivation, their work in clinical practice, increases criticism acceptance, better adaptation to stress and giving attention to the educational content obtainable by the clinical instructor. [16,17] Therefore, it is noted that the items in the teaching ability, evaluation and nursing competence respectively,interpersonal relations, and personality categories are nurturing actions consistent with the overall nursing principle of caring.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, student-teacher communication affects students' attitudes. [3] The findings of this study differed from Western studies where students rated communication skills as the most important domains. [26] In the clinical practice environment, faculty may interpret these behaviors to have potential to be less well received by students than in a classroom environment and therefore may have used them less frequently.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…17 Behavior of teachers has an eminent source that affects nursing students learning. 18 The most enhancing factors for the learning of nursing students are "Regular and punctual for class, good communication skills, encouraging the students to participate in class, while punishing students, threatening them and discouraging negatively impacts students learning.…”
Section: Funding Sources: Nonementioning
confidence: 99%
“…As a result, instructors should have a major influence on student behavior, which is shown in instructors' caring behavior. The clinical instructor should provide high-quality and safe healthcare to all categories of society, thereby influencing the self-efficacy of students (4) .…”
Section: Introductionmentioning
confidence: 99%